Effects of particulate air pollution exposure on lung-brain axis and related miRNAs modulation in mouse models - Giammona, Alessandro; Terribile, Giulia; Rainone, Paolo; Pellizzer, Chiara; Porro, Danilo; Cerasa, Antonio; Sancini, Giulio; Rashid, Ameen-Ur; Belloli, Sara; Valtorta, Silvia; Lo Dico, Alessia; Bertoli, Gloria (Frontiers in Cell and Developmental Biology, 2025)
Particulate matter exposure is linked to numerous health issues, including respiratory, cardiovascular, and neurodegenerative diseases. This review focuses on the biological mechanisms through which air pollution influences the lung-brain axis, highlighting the role of miRNAs in regulating gene pathways affected by PM. Some microRNAs (miRNAs) are identified as key modulators of cellular processes, including inflammation, epithelial-to-mesenchymal transition (EMT), and blood-brain barrier integrity. Using mice models to study these effects allows for controlled experimentation on the systemic distribution of PM across biological barriers. Among the imaging technologies, Positron Emission Tomography is the best approach to monitor the distribution and effects of PM in vivo. The research underscores the importance of miRNA profiles as potential markers for the health effects of PM exposure, suggesting that specific miRNAs could serve as early indicators of damage to the lung-brain axis.